ASPEK KEPERDATAAN PERKAWINAN BEDA AGAMA YANG TIDAK TERCATAT DI PENCATATAN SIPIL PASCA TERBITNYA SURAT EDARAN MAHKAMAH AGUNG NOMOR 2 TAHUN 2023 TENTANG PETUNJUK BAGI HAKIM DALAM MENGADILI PERKARA PERMOHONAN ANTAR-UMAT YANG BERBEDA AGAMA DAN KEPERCAYAAN - Faot, Retna Yelmidiany; Hedewata, Agustinus; Nubatonis, Orpa J (Petitum Law Journal, 2024)
Interfaith marriages are a serious legal problem because apart from involving different regulations which can conflict with each other, they can also result in civil rights not being fulfilled for interfaith couples whose marriages are not registered by the state. Due to the large number of cases of interfaith marriages, the Supreme Court issued Supreme Court Circular Letter Number 2 of 2023 concerning Instructions for Judges in Adjudicating Cases on Applications for Registration of Marriages Between People of Different Religions and Beliefs. The arrangements listed in number 2 (two) of SEMA Number 2 of 2023 can prevent couples of different religions from obtaining a marriage certificate approved by the state. Interfaith couples whose marriages are not registered by the state may lose their civil rights if SEMA Number 2 is implemented in 2023.